Ecosystem services scenario simulation in Guangzhou based on the FLUS-InVEST model - Dafang Wu; Jizhen Mo; Lechun Zeng; Ping Zhou; Muyun Xie; Haobin Yuan (Scientific Reports)
Abstract The sustainable development of the region cannot be separated from the support of ecosystem services. By investigating the effects of potential land use and land cover change (LUCC) on these services in different scenarios, we can work towards protecting the ecological environment of urban areas, thus promoting the sustainable development of the region. This paper simulates the natural, ecological and development scenarios of Guangzhou in 2035 using the FLUS model based on LUCC of Guangzhou from 2015 to 2020; on top of the three scenarios, calculates the physical quantities of three ecosystem services—annual water yield, habitat quality, and carbon storage, through the InVEST model; and uses the GeoDetector model to identify the influencing Drivers. (1) Compared to 2020, the different land use types will change differently under the three scenarios in 2035; (2) The spatial distribution of ecosystem services in Guangzhou for the years 2020 and 2035 show similar patterns across three scenarios; (3) Based on the analysis of the driving factors behind Land Use and Land Cover Change (LUCC) in Guangzhou, it has been observed that population density has the most significant impact on LUCC.